2019
DOI: 10.1111/adb.12720
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA methyltransferase activity in cocaine treatment and withdrawal in the nucleus accumbens of mice

Abstract: An increasing number of reports have provided crucial evidence that epigenetic modifications, such as DNA methylation, may be involved in initiating and establishing psychostimulant‐induced stable changes at the cellular level by coordinating the expression of gene networks, which then manifests as long‐term behavioral changes. In this study, we evaluated the enzyme activity of DNA methyltransferases (DNMTs) after cocaine treatment and during withdrawal. Furthermore, we studied how genetic or pharmacological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…We suppose that this increase in Dnmt3b mRNA levels in the NAc is a regulatory mechanism and that DNMTs compensate for each other's functions. This speculation is supported by the reports that demonstrate that Dnmt3b functionally compensates for Dnmt1 deficiency in intestinal epithelium and Dnmt3a silencing in the NAc (Elliott et al, 2016;Urb et al, 2019). Comparable to Dnmt3b mRNA levels in the NAc, we found that RC exposure significantly increased the mRNA levels of Tet3 in the NAc of HE rats.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We suppose that this increase in Dnmt3b mRNA levels in the NAc is a regulatory mechanism and that DNMTs compensate for each other's functions. This speculation is supported by the reports that demonstrate that Dnmt3b functionally compensates for Dnmt1 deficiency in intestinal epithelium and Dnmt3a silencing in the NAc (Elliott et al, 2016;Urb et al, 2019). Comparable to Dnmt3b mRNA levels in the NAc, we found that RC exposure significantly increased the mRNA levels of Tet3 in the NAc of HE rats.…”
Section: Discussionsupporting
confidence: 85%
“…Accumulating data suggest that epigenetic modifications within brain reward circuits, for example, in nucleus accumbens (NAc), may be key regulators of the persistent changes in brain plasticity and gene expression related to addiction (Nestler, 2014). We and other groups have demonstrated that DNA methylation (DNAm), the addition of a methyl group to Position 5 of the cytosine (5-mC), plays a role in psychostimulant-induced changes in gene expression and behaviour (Anier et al, 2010(Anier et al, , 2018LaPlant et al, 2010;Massart et al, 2015;Nielsen et al, 2012;Pol Bodetto et al, 2013;Tian et al, 2012;Urb et al, 2019). In addition, studies have indicated that the lateral habenula (LHb) might play an important role in reward and drug addiction mechanisms (Jhou et al, 2013;Lecca et al, 2014;Matsumoto and Hikosaka, 2007;Shelton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The enduring effects of these drugs, even after long periods of abstinence, have suggested the presence of persistent molecular events caused by transcriptional, epigenetic and translational changes [1] within addictionrelated brain regions [2], such as the nucleus accumbens (NAc), prefrontal cortex (PFC), and hippocampus. Notably, accumulating evidence has revealed an important role of epigenetic regulation in the effects of psychostimulants [3](e.g., cocaine [4,5]) and identi ed the involvement of modi cations of histones present in chromatin [6,7], DNA methylation [8,9], and DNA hydroxymethylation in the development of addiction. With respect to METH, however, only a few studies have investigated the epigenetic effects of these drugs, mainly focusing on the NAc and striatum [10][11][12][13][14].…”
mentioning
confidence: 99%
“…Furthermore, acute and repeated cocaine treatment leads to the hypermethylation of fosB promoter associated CpG islands in the NAc. Additionally, Mari Urb et al [ 38 ] reported that the expression of DNMT-3b in the postnatal mouse brain is relatively low compared to that of DNMT-1 and DNMT-3a. Interestingly, acute (0.5–3 h) exposure to cocaine reduces the mRNA expression of DNMT-1 and DNMT-3a in the NAc, which indicates that cocaine regulates DNMT mRNA expression in a time-dependent manner [ 39 ].…”
Section: Discussionmentioning
confidence: 99%